Are house prices in the Norwegian capital too high?. Issue 2 (1st June 2015) - Krakstad, Svein Olav; Oust, Are
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to investigate whether the homes in the Norwegian capital, Oslo, are overpriced. While house prices in many countries dropped after the financial crisis, those in Norway have continued to increase. Over the past 20 years, real house prices in Oslo have increased by around 7 per cent yearly. Design/methodology/approach – The authors use a vector error correction model to estimate the equilibrium between house prices, rents, construction costs and wages to examine whether house prices in Oslo are overpriced. Findings – Long-term relationships between house prices, rents, construction costs and wages are found and used to estimate equilibrium house prices in Oslo. The overpricing in Oslo compared to estimated equilibrium prices is around 35 per cent. Practical implications – Price–rent, price–construction cost and price–income ratios are often used, by practitioners to say something about over- or underpricing in the housing market. We test and find that house prices, rents and construction costs move toward constant ratios in the long run, while wages are found to be weakly exogenous in the system. Originality/value – Our estimate of overpricing gives households, investors and policy-makers a better understanding of the risk associated with owning dwellings.